The Seven-Year Cost-Effectiveness of Anterior Cervical Discectomy and Fusion Versus Cervical Disc Arthroplasty: A Markov Analysis. Issue 22 (15th November 2018) - Kim, Jun S.; Dowdell, James; Cheung, Zoe B.; Arvind, Varun; Sun, Li; Jandhyala, Chanakya; Ukogu, Chierika; Ranson, William; Jacobs, Samantha; McAnany, Steven; Cho, Samuel Kang-Wook
Abstract : Study Design: Markov model analysis. Objective: The aim of this study was to determine the 7-year cost-effectiveness of single-level anterior cervical discectomy and fusion (ACDF) versus cervical disc replacement (CDR) for the treatment of cervical disc degeneration. Summary of Background Data: Both ACDF and CDR are acceptable surgical options for the treatment of symptomatic cervical disc degeneration. Past studies have demonstrated at least equal effectiveness of CDR when compared with ACDF in large randomized Investigational Device Exemption (IDE) studies. Short-term cost-effectiveness analyses at 5 years have suggested that CDR may be the preferred treatment option. However, adjacent segment disease and other postoperative complications may occur after 5 years following surgery. Methods: A Markov model analysis was used to evaluate data from the LDR Mobi-C IDE study, incorporating five Markov transition states and seven cycles with each cycle set to a length of 1 year. Transition state probabilities were determined from complication rates, as well as index and adjacent segment reoperation rates from the IDE study. Raw SF-12 data were converted to health state utility values using the SF-6D algorithm for 174 CDR patients and 79 ACDF patients. Results: Assuming an ideal operative candidate who is 40-years-old and failed appropriate conservative care, the 7-year cost was $103, 924 for ACDF and $105, 637 for CDR. CDR resulted in the generation of 5.33 quality-adjusted life-years (QALYs), while ACDF generated 5.16 QALYs. Both ACDF and CDR were cost-effective, but the incremental cost-effectiveness ratio (ICER) was $10, 076/QALY in favor of CDR, which was less than the willingness-to-pay (WTP) threshold of $50, 000/QALY. Conclusion: ACDF and CDR are both cost-effective strategies for the treatment of cervical disc degeneration. However, CDR is the more cost-effective procedure at 7 years following surgery. Further long-term studies are needed to validate the findings of this model. Level of Evidence: 1